Entrepreneurial Alertness An Exploratory Study - Li, Zhineng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Entrepreneurial alertness plays an important role in the processes of opportunity exploration and exploitation. A central thesis of this dissertation is that opportunity creation requires a certain transformation of an individual entrepreneur's mental schema. A four-dimension structure of the entrepreneurial alertness construct is created, namely juxtaposing, unlearning, prospecting and embellishing. A comprehensive model of entrepreneurial alertness are adopted and tested via structural equation modeling on the basis of survey data from 1080 entrepreneurs in two coastal regions of P. R. China.
Keywords: Economics; Entrepreneurship; Economics/Management Science; Entrepreneurship